Fool the markets?: Creative accounting, fiscal transparency and sovereign risk premia - Kerstin Bernoth; Guntram B. Wolff (Center for Economic Studies and ifo Institute (CESifo), 2006)
We investigate the effects of official fiscal data and creative accounting signals on interest rate spreads between bond yields in the European Union. Our model predicts that risk premia contained in government bond spreads should increase in both the official fiscal position and the expected creative part of fiscal policy. The relative importance of these two signals depends on the transparency of the country. Greater transparency reduces risk premia. The empirical results confirm the hypotheses. Creative accounting increases the spread. The increase of the risk premium is stronger if financial markets are unsure about the true extent of creative accounting. Fiscal transparency reduces risk premia.
Keywords: G12; E43; E62; H6; F34; 330; Haushaltsdefizit; Öffentliche Schulden; Bilanzpolitik; Konvergenzkriterien; Zinsdifferenz; Länderrisiko; Risikoprämie; Öffentliche Anleihe; Schätzung; EU-Staaten